Critical success factors in IT projects : challenges and effectiveness - Xing Jia, Tan (2014)
Information Technology (IT) projects have bigger contribution to the country economy and development. However, IT project management is a crucial task because many IT projects failed due to project delayed, over budget or not achieved the planned scope. The main objectives of this research are identifying critical success factors in IT projects and to investigate the challenges and effectiveness of the critical factors in IT projects. Meanwhile, this research also investigates the relationships between critical success factors and IT project success. A research framework with 7 critical success factors was developed based on the thorough literature review. These 7 factors are collected based on their importance to IT projects and their repeated occurrence in the literature related to the critical success factors. Surveying method has been used to collect data and the data collected are being analysed by using Statistical Package for the Social Sciences (SPSS) software. The respondents are selected from the IT companies that are located in Kuala Lumpur and Selangor with a Multimedia Super Corridor (MSC) status under the InfoTech group. This research is useful for IT companies where project managers can benefit from the mentioned critical success factors by concentration on them while planning and executing IT projects. From the results, it is observed that there are positive significance relationships between two (2) critical success factors and IT project success. Therefore, the results are significant to enhance the success rates of IT projects in Malaysia